Tridharma Religion in Indonesia: Reading Hikmah Tridharma and Tjahaja Tri-Dharma Magazines during the 1970s-1980s - Deni Miharja; Setia Gumilar; Asep Sandi Ruswanda; Moh Zaimil Alivin (UIN Sunan Gunung Djati Bandung, 2022)
In religious conversations, syncretism is often perceived negatively even though it is actually a healthy process. One form of syncretism that emerged in Indonesia is the religion of Tridharma which consists of Buddhism, Confucianism, and Daoism. This paper discusses syncretism in the religion of Tridharma in Indonesia. Using a historical approach during the 1970s, this paper is a literature study of two magazines affiliated with the religion of Tridharma, namely the Hikmah Tridharma magazine and the Tjahaja Tri-Dharma magazine. This paper rethinks the concept of syncretism as a dirty word, or at least negative form, to one of neutrality. Considering religion as dynamic, syncretism in the religion of Tridharma or Sam Kauw has been a historical process since the Ming dynasty in Mainland China. The Hikmah Tridharma magazine and the Tjahaja Tri-Dharma magazine during the 1970s illustrate how syncretism in the body of Tridharma religion occurs not only between Buddism, Confucianism, and Daoism but also with Hinduism and group of theosophy. As one element of the dynamics of religious belief, the politics of recognition is important. In Indonesia, the state gave a different attitude to Chinese religions or all things Chinese-affiliated in general during the New Order era, and the era of transition to reform, Gus Dur. This then triggered contestation between Chinese religions themselves in Indonesia, especially between the religion of Tridharma and Confucianism.